α,25(OH)2D3 Promotes oxidative stress in endothelial cells transformed by vGPCR - Tapia, Cinthya Mariela (2020)
The infectious cause of Kaposi’s sarcoma (KS) neoplasm is KS-associated Herpesvirus (KSHV or human herpesvirus 8). Furthermore, virally G Protein-coupled Receptor (vGPCR) is one of the molecules from the lytic phase able to induce KS associated cellular modifications through paracrine oncogenesis. We have previously demonstrated that 1α,25(OH)2D3 exerts antiproliferative effects on endothelial cells that stably express vGPCR by inhibiting NF-κB pathway and promoting apoptosis and autophagy. Oxidative stress is frequent in many types of cancer where reactive oxygen species (ROS) can act as a promoting or suppressing agent. In this work, our goal was to study the involvement of ROS as part of the antineoplastic mechanisms triggered by 1α,25(OH)2D3 in vGPCR cells. By a spectrofluorimetric method using the H2-DCF-DA probe, ROS levels were detected higher than control conditions after 1α,25(OH)2D3 (10 nM, 24 or 48 h) treatment. When VDR expression was knocked down by shRNA against VDR (vGPCR-shVDR cell line), ROS increase was found to be VDR dependent (48 h). Our previous reports indicated that vGPCR cells proliferation decreases at 80% after 1α,25(OH)2D3 treatment, triggering cell cycle arrest and apoptosis by a mechanism dependent on the caspase-3 cleavage. In this case, Western blot studies showed an increase expression of pro-apoptotic proteins like BIM and caspase-3 cleavage by 1α,25(OH)2D3 (10 nM, 48 h) and no reversal effect by N-Acetyl-cysteine (1 mM) antioxidant was observed. Altogether, these preliminary results suggest that ROS levels promotion by 1α,25(OH)2D3 through VDR, triggers apoptosis-related mechanisms on vGPCR cells.